2018
DOI: 10.14735/amko2018110
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Metastatic Renal Cell Carcinoma

Abstract: SouhrnVýchodiska: Zhoubné nádory ledvin představují přibližně 2-3 % všech malignit. Česká republika celosvětově dosahuje prvenství v incidenci zhoubných nádorů ledvin. Nejčastější je světlobuněčný karcinom, který představuje přibližně 70 % všech renálních karcinomů. V léčbě metastatického renálního karcinomu (metastatic renal cell cancer -mRCC) došlo v poslední době k významnému rozšíření léčebných možností. Léčba zahrnuje antiangiogenní přístup inhibicí receptoru pro vaskulární endoteliální růstový faktor, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…This is similar to the global incidence of 337 000 cases with 143 000 deaths 5. The Czech Republic has the highest incidence of RCC worldwide 1. Some have suggested that arsenic exposure or higher rates of smoking and obesity (smoking increases the risk of RCC by 50% in male and 20% in female smokers, and 5 kg/m 2 increments in body mass index (BMI) increase the risk of RCC by 24% in men and 34% in women) are to blame, but surrounding countries such as Slovakia do not have a large enough difference in risk factors for this to be the case 6.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is similar to the global incidence of 337 000 cases with 143 000 deaths 5. The Czech Republic has the highest incidence of RCC worldwide 1. Some have suggested that arsenic exposure or higher rates of smoking and obesity (smoking increases the risk of RCC by 50% in male and 20% in female smokers, and 5 kg/m 2 increments in body mass index (BMI) increase the risk of RCC by 24% in men and 34% in women) are to blame, but surrounding countries such as Slovakia do not have a large enough difference in risk factors for this to be the case 6.…”
Section: Discussionsupporting
confidence: 74%
“…Renal cell carcinoma (RCC) is a common cancer, believed to make up 2%–3% of all cancers worldwide 12.…”
Section: Introductionmentioning
confidence: 99%
“…Renal cell carcinoma has a worse prognosis and easily develop metastatic disease, which are usually incurable, and the median survival of metastatic RCC patients is significantly worse . Currently, the treatments for RCC have evolved from conventional drugs to biologic targeting therapies, among which cytokines are the most crucial therapeutic targets . However, the existing therapies for RCC are not satisfactory owing to the low efficacy in suppressing disease activity as well as the adverse effects in patients.…”
Section: Discussionmentioning
confidence: 99%
“…29 Currently, the treatments for RCC have evolved from conventional drugs to biologic targeting therapies, among which cytokines are the most crucial therapeutic targets. 30,31 However, the existing therapies for RCC are not satisfactory owing to the low efficacy in suppressing disease activity as well as the adverse effects in patients. In this study, H1 nanoparticles with a low toxicity were applied in the delivery system of targeting therapeutic.…”
Section: Discussionmentioning
confidence: 99%
“…The distal metastases are usually found in the beginning of diagnosis or after primary tumor resection in a majority of patients with advanced renal carcinoma (3). Treatment of metastatic renal carcinoma is currently focused on antiangiogenic agents, cytokines, and mAbs (4). Although these agents have greatly improved patient survival in the development of advanced renal carcinoma treatment, the therapeutic effect, potentially serious side effects, and high drug costs are still not satisfactory (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%